The Demand for Commodity Insurance by Developing Country Agricultural Producers : Theory and an Application to Cocoa in Ghana - Sarris, Alexander (World Bank, Washington, DC, 2014)
The author considers the benefit to agricultural producers of commodity price insurance that provides in every year-but in advance of the resolution of production and price uncertainty--a minimum price for a fixed or variable portion of production. Under the assumption that producers do not change their long term production and income diversification pattern, the author suggests a theoretical framework that leads to explicit formulas of the benefit in providing this type of insurance. He shows that this benefit depends not only on the actuarially fair insurance premium, but also on household-specific factors that depend on the attitudes to risk, the consumption smoothing parameters, and the household-specific exposures to income risks. The author applies the theoretical framework for Ghana, using the Ghana Living Standards Survey data to specify various classes of cocoa-producing households and monthly price data for both domestic and international prices, to formulate appropriate models for ascertaining price risks faced by producers. The author gives empirical estimates of the actuarially fair premium, and shows that they are smaller than market-based put option prices from organized exchanges. The overall benefit in providing minimum price insurance to households, however, turns out to be substantially higher than the actuarially fair premiums and the market-based put option prices. This is due to both the magnitude of the uncertainties facing the households, as well as their risk and consumption smoothing behavior.